Pengeloaan Sampah Organik Melalui Pembuatan Eco enzyme di Desa Tanjung Bulan, Kabupaten Kaur - Danang Adi Putra; Leony Carvio Rahma Dianty; Resti Rahmadani; Liya Rahmadani; Fadiah Hazirah; Perdian Pebri Teriyadi (PT. Penerbit Riset Sadwa, 2026)
The increasing amount of household organic waste that is not properly managed remains a significant environmental issue, contributing to pollution and public health risks. This community service program aimed to improve community knowledge and practical skills in processing household organic waste into eco-enzyme as an environmentally friendly and value-added waste management solution. The implementation methods included educational sessions on organic waste management, demonstrations of eco-enzyme production, hands-on practice by participants, and assistance throughout the fermentation process. The results indicated an improvement in participants' understanding of organic waste management principles and their ability to independently.